PENGARUH KUALITAS LAYANAN TERHADAP CITRA INSTITUSI DAN KEPERCAYAAN MAHASISWA PADA PERGURUAN TINGGI SWASTA DI PROVINSI GORONTALO - Deby Rita Karundeng (International Interdisciplinary Conference on Sustainable Development Goals, 2018)
This study aims to analyzed direct and indirect influences of services quality on institutional image and confidence of students at private universities in Gorontalo Province. This type of research is descriptive research to explains causality relationship between variables through hypothesis. The data used primary data collected through the distribution of questionnaires at nine private universities in Gorontalo with population 15,543 studenst and the sample size is 200 respondent. Data analysis techniques use the structural equation model (SEM). The result in these studied is 1) the direct service quality have a significant effect to the institution image, 2) service quality have a significant effect to the confidence of students, 3) institution image have a significant effect to the confidence of students, 4) indirectly service quality have positive and significant influence to confidence of student's through institution image